Low Enrollment of Adolescents and Young Adults Onto Cancer Trials: Insights From the Community Clinical Oncology Program - Roth, Michael E. (J Oncol Pract, 2016)
PURPOSE: Stagnant outcomes for adolescents and young adults (AYAs; 15 to 39 years old) with cancer are partly attributed to poor enrollment onto clinical trials. The National Cancer Institute (NCI) Community Clinical Oncology Program (CCOP) was developed to improve clinical trial participation in the community setting, where AYAs are most often treated. Further, many CCOP sites had pediatric and medical oncologists with collaborative potential for AYA recruitment and care. For these reasons, we hypothesized that CCOP sites enrolled proportionately more AYAs than non-CCOP sites onto Children’s Oncology Group (COG) trials. METHODS: For the 10-year period 2004 through 2013, the NCI Division of Cancer Prevention database was queried to evaluate enrollments into relevant COG studies. The proportional enrollment of AYAs at CCOP and non-CCOP sites was compared and the change in AYA enrollment patterns assessed. All sites were COG member institutions. RESULTS: Although CCOP sites enrolled a higher proportion of patients in cancer control studies than non-CCOP sites (3.5% v 1.8%; P < .001), they enrolled a lower proportion of AYAs (24.1% v 28.2%, respectively; P < .001). Proportional AYA enrollment at CCOP sites decreased during the intervals 2004 through 2008 and 2009 through 2013 (26.7% v 21.7%; P < .001). CONCLUSION: Despite oncology practice settings that might be expected to achieve otherwise, CCOP sites did not enroll a larger proportion of AYAs in clinical trials than traditional COG institutions. Our findings suggest that the CCOP (now the NCI Community Oncology Research Program) can be leveraged for developing targeted interventions for overcoming AYA enrollment barriers.